Praktik Murabahah pada Perbankan Syariah di Kendari - Ummi Kalsum (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2017)
This study aims to determine the murabahah financing practices in Islamic banking with a case study in Kendari Branch BMI. This research employs the qualitative research and descriptive explorative research by implementing interview technique, observation and documentation. The collected data then processed and analysed by step reduction, presentation and conclusion. The approach used in this research is normative juridical. The results show that the determination of the law murabahah based on Muslim scholars judgement (ijma’) because Muslims have been practicing since the first trading murabahah. Murabahah must not conflict with sharia and regulated in Law No.21 of 2008 concerning Islamic Banking and fatwas DSN-MUI related to murabahah. While based on the results of research in the field of murabahah financing practiced in Kendari Branch BMI is generally in accordance with the provisions set forth by Law No.21 of 2008 concerning Islamic Banking and DSN MUI fatwas both in terms of the parties, the contract murabahah contract pillars, steps murabaha applicable on Islamic banking in Indonesia and some provisions relating to the financing murabaha.